Developing the Capacity of Post-Conflict Countries through South-South Partnerships - Muthayan, Saloshini (2012)
Following years of war and devastation, the citizens of post-conflict countries look to the government with high expectations for a better quality of life. These countries, however, face severe institutional and human capacity constraints and normally have no other option than turning to donors for help in reconstructing their societies.